Image recognition technique of road tax sticker in Malaysia - Alharaki, Omarah Omar; Zeki, Akram M. (2012)
Plate Recognition became significant in daily life because of the unlimited increase of transportation systems which make it impossible to be fully managed and monitored by humans, examples are so many like traffic monitoring, tracking stolen cars, managing parking toll, red-light violation enforcement, border, toll gates and customs check points. This paper will propose a new image recognition technique for inspecting the validity of car Road Tax information in Malaysia based on Neural Network. The development of vehicle Road Tax Recognition (RTR) System will result in greater efficiency for vehicle monitoring system at Toll Gates in Malaysia. In Malaysia, the usage of recognition system is limited to the vehicle plates. It means that the system is unable to detect Road Tax stickers. Therefore, The Implementing of the Image Recognition of The Road Tax and Monitoring the License Plate Number Identification system helps to automatically detect the Road Tax sticker information and plate number. Previously, the police used to observe the expiry date of the Road Tax sticker and matched it with the car plate number manually. So this paper aimed to propose a technique to monitor the vehicle by automatically capturing and extracting the Road Tax sticker image.